A Fixed Point Approach to the Stability of Quadratic Functional Equation with Involution. (10th June 2008) - Jung, Soon-Mo; Lee, Zoon-Hee
Abstract : Cădariu and Radu applied the fixed point method to the investigation of Cauchy and Jensen functional equations. In this paper, we will adopt the idea of Cădariu and Radu to prove the Hyers-Ulam-Rassias stability of the quadratic functional equation with involution.